Conditional control of fluorescent protein degradation by an auxin-dependent nanobody - Katrin Daniel (Nature Portfolio, 2018)
Current approaches to conditionally deplete target proteins require site-specific genetic engineering or have poor temporal control. Here the authors overcome these limitations by combining the AID system with nanobodies to reversibly degrade GFP-tagged proteins in living cells and zebrafish.